Sharia Entrepreneur Internship Method In Building Marhamism Character In Islamic Boarding Schools - Erick Yusuf; Endin Mujahidin (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The background of this research is that Islamic boarding schools as one type of Islamic educational institution in Indonesia, have been empirically proven to be able to develop students from various aspects, including intellectual, emotional, and religious character formation so that the output of Islamic boarding schools is born that has good knowledge and character. The purpose of this study was to examine the Islamic entrepreneurship apprenticeship method in fostering the character of Marhamis in Islamic boarding schools. The method used is the library research method. The method can realize ideas and is used to determine the validity of a study, using various techniques. The results showed that the Islamic entrepreneurship apprenticeship method in fostering the character of Marhamis in Islamic boarding schools through exemplary methods, advice, habituation, stories, motivation, and persuasion. The hope is that students can become people who have an independent spirit, liberate others, are independent, entrepreneurial, empathetic, patient, able to control themselves, work together, and love.